2018
DOI: 10.1111/epi.14070
|View full text |Cite
|
Sign up to set email alerts
|

Nonconvulsive status epilepticus in rats leads to brain pathology

Abstract: These findings provide evidence for a significant brain pathology following NCSE in an experimental rodent model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 43 publications
(106 reference statements)
2
36
0
Order By: Relevance
“…The descriptions did not include the variety of electrographic patterns revealed by our initial analysis of EEG in rats with lateral FPI. Nor did the descriptions of EEG patterns in rats during NCSE induced with hippocampal stimulation 28 or in rats with repeated unprovoked seizures and interictal epileptiform activity with subtle behavioral symptoms induced by ballistic TBI 29 correspond to the EEG patterns observed in our animals. Rather, the electrographic patterns we observed corresponded to those described in human complex partial SE after brain injury.…”
Section: Lateral Fpi Induces Ncsementioning
confidence: 61%
“…The descriptions did not include the variety of electrographic patterns revealed by our initial analysis of EEG in rats with lateral FPI. Nor did the descriptions of EEG patterns in rats during NCSE induced with hippocampal stimulation 28 or in rats with repeated unprovoked seizures and interictal epileptiform activity with subtle behavioral symptoms induced by ballistic TBI 29 correspond to the EEG patterns observed in our animals. Rather, the electrographic patterns we observed corresponded to those described in human complex partial SE after brain injury.…”
Section: Lateral Fpi Induces Ncsementioning
confidence: 61%
“…In two studies, contralateral hippocampal alterations were observed when a convulsive status epilepticus was promoted using either high doses of unilaterally injected KA 37 or repeated unilateral hippocampal stimulation. 38 In a recent report, unilateral hippocampal electrical stimulation in rats demonstrated cell loss and changes in the expression of N-cadherin in the hippocampus contralateral to stimulation 39 exclusively in a subgroup of animals that developed seizures 4 weeks after ncSE. Of interest, contralateral neuronal loss was not observed in rats submitted to ncSE that did not develop spontaneous seizures in the chronic phase.…”
Section: Discussionmentioning
confidence: 96%
“…39 We utilized postfixed tissue because it allows longer MR scanning times that improve imaging definition without altering the significance of the recorded signals; apparent diffusion coefficient (ADC) measurements in fixed brains are characterized by lower values compared to in vivo condition. These data confirmed the results of the above-mentioned study on the ncSE model induced by unilateral electrical stimulation of one hippocampus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People with epilepsy or epileptic encephalopathy often develop ongoing NCSE after status epilepticus (SE) with prominent motor activity (convulsive SE) ( 1 4 ). Functional outcome and prognosis may be worse in patients with ongoing NCSE due to increased metabolic demand and thus causing secondary brain damage ( 5 8 ). Recent studies show mortality of up to 40% in super-refractory SE and increased costs and length of stay associated with refractory course ( 9 ).…”
Section: Introductionmentioning
confidence: 99%